Unraveling the Diversity of Eukaryotic Microplankton in a Large and Deep Perialpine Lake Using a High Throughput Sequencing Approach - Salmaso, Nico; Boscaini, Adriano; Pindo, Massimo (Frontiers in Microbiology, 2020)
The structure of microbial communities, microalgae, heterotrophic protozoa and fungi contributes to characterize food webs and productivity and, from an anthropogenic point of view, the qualitative characteristics of water bodies. Traditionally, in freshwater environments many investigations have been directed to the study of pelagic microalgae (“phytoplankton”) and periphyton (i.e. photosynthetic and mixotrophic protists) through the use of light microscopy (LM). While the number of studies on bacterioplankton communities have shown a substantial increase after the advent of high-throughput sequencing (HTS) approaches, the study of the composition, structure, and spatio-temporal patterns of microbial eukaryotes in freshwater environments was much less widespread. Moreover, the understanding of the correspondence between the relative phytoplankton abundances estimated by HTS and LM is still incomplete. Taking into account these limitations, this study examined the biodiversity and seasonality of the community of eukaryotic microplankton in the epilimnetic layer of a large and deep perialpine lake (Lake Garda) using HTS. The analyses were carried out at monthly frequency during 2014 and 2015. The results highlighted the existence of a rich and well diversified community and the presence of numerous phytoplankton taxa that were never identified by LM in previous investigations. Furthermore, the relative abundances of phytoplankton estimated by HTS and LM showed a significant relationship at different taxonomic ranks. In the two years of investigation, the temporal development of the whole micro-eukaryotic community showed a clear non-random and comparable distribution pattern, with the main taxonomic groups coherently distributed in the individual seasons. In perspective, the results obtained in this study highlight the importance of HTS approaches in assessing biodiversity and the relative importance of the main protists groups along environmental gradients, including those caused by anthropogenic impacts (e.g. eutrophication and climate change).